The Synergistic Effect of Different Antibiotics Against Mastitis Associated Escherichia coli in Pakistan - Iqbal, Muhammad Kaleem; Sultan, Hafiz Muhammad; Bashir, Bakhtawar; Aslam, Rizwan; Ali, Sultan; Niazi, Adnan Khan (Universitas Airlangga, 2025)
Background: Escherichia coli is a Gram-negative, short rod-shaped, non–spore forming bacterium that acts as a pathogen in both humans and animals. It plays a major role in mastitis, one of the most challenging and economically important diseases affecting dairy animals worldwide. Purpose: This study aimed to isolate multidrug-resistant (MDR) E. coli from milk samples collected from dairy farms and to evaluate the synergistic effects of different antibiotic combinations against these isolates. Method: Escherichia coli was isolated using MacConkey agar and identified through biochemical testing. Antibiotic susceptibility testing (AST) was performed using the Kirby–Bauer disk diffusion method to identify MDR isolates. Minimum inhibitory concentrations (MICs) were determined via the broth microdilution method. To assess potential synergism, fractional inhibitory concentration (FIC) indices were calculated, and 252 antibiotic combinations were tested. Results: Most E. coli isolates were resistant to multiple antibiotics, except meropenem and vancomycin. Among all tested combinations, 22 pairs such as meropenem–amoxicillin, meropenem–enrofloxacin, amoxicillin–colistin, enrofloxacin–colistin, ceftriaxone–colistin, ceftriaxone–oxytetracycline, and others exhibited synergistic effects. Several additional combinations showed additive effects, suggesting potential utility in combating multidrug resistance in E. coli associated with mastitis. Conclusion: The FIC analysis revealed that combinations of meropenem with amoxicillin (Mer+Amox), meropenem with enrofloxacin (Mer+Enro), and colistin with amoxicillin (Col+Amox) demonstrated the strongest synergistic activity. These results indicate that specific antibiotic combinations could provide promising therapeutic strategies against MDR E. coli infections in mastitis cases.